THE EFFECT OF EDUCATIONAL BOOKLETS ON KNOWLEDGE AND ATTITUDE ABOUT COVID-19 VACCINATION - Diki; Fatonah, Sofa; Astuti, Reini (STIKes Budi Luhur Cimahi, 2024)
The global outbreak of the Coronavirus (COVID-19) caused by the SARS-CoV-2 virus has been going on since 2019. Indonesia is one of the countries affected by the spread of the COVID-19 infectious disease. One strategy for the spread of the COVID-19 virus throughout Indonesia is the COVID-19 technique. For the community to remain socially and economically productive, the COVID-19 vaccination aims to develop community group immunity (herd immunity) and become the reason for protecting the community from COVID-19. This study aims to determine the effect of educational media books on knowledge and attitudes about COVID-19 vaccination in Parigi village, Sindangsari village. This study uses a quantitative experimental method. Determination of respondents by using purposive sampling and obtained respondents as many as 17 people. Collecting data by giving a questionnaire technique. The results of this study indicate an increase in public knowledge after being given booklet media education as much (23.6%). For attitudes, there is an increase in the positive attitude of the community as much (5.9%). This means that there is an influence of educational media books on knowledge about COVID-19 vaccination in Parigi village, Sindangsari village. This is to the theory of Notoatmodjo (2005) Knowledge is the result of knowing and occurs after people sense a certain object, the attitude of the mental state of readiness, which is regulated through experience which influences individual respondents on all related objects and situations. with him. Hopefully, with the results of this study, the public can better understand health problems, especially vaccination, besides that the Sindangsari village and related health centers can assist in carrying out health education to the community regarding existing health issues. Keywords: Influence, Education, Booklet Media, Covid-19 Vaccination